2020
DOI: 10.1155/2020/4347676
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Relationship between Structural and Functional Imaging of Cerebrovascular Disease and Cognition-Related Fibers

Abstract: In order to assess the relationship between structural and functional imaging of cerebrovascular disease and cognition-related fibers, this paper chooses a total of 120 patients who underwent cerebral small vessel disease (CSVD) treatment at a designated hospital by this study from June 2013 to June 2018 and divides them into 3 groups according to the random number table method: vascular dementia (VaD) group, vascular cognitive impairment no dementia (VCIND) group, and noncognition impairment (NCI) group with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…T2DM is related to an increased risk of cognitive impairment. T2DM patients with high blood GV had increased cognitive decline[ 8 ]. According to this study, GV was an influencing factor for increased infarct burden in lacune patients combined with T2DM, and increased GV increased the risk of cognitive impairment in lacune patients complicated with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T2DM is related to an increased risk of cognitive impairment. T2DM patients with high blood GV had increased cognitive decline[ 8 ]. According to this study, GV was an influencing factor for increased infarct burden in lacune patients combined with T2DM, and increased GV increased the risk of cognitive impairment in lacune patients complicated with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The destruction of cerebral vascular structure causes cerebral vascular autoregulation dysfunction, and can lead to the occurrence of amyloid angiopathy, which continuously reduces the cognitive function of patients, resulting in cognitive dysfunction[ 38 ]. In addition, increasing evidence has shown that the cerebellum is related to cognitive function, the prefrontal and the cerebellum cortex have extensive connections, and the cell damage of these connection could explain the cognitive decline in patients with cerebellar ischemia[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polypharmacy was defined as the concomitant use of five or more medications [ 21 , 22 ]. Cognition was assessed using the Clock Drawing Test (CDT), where participants received one point for clock contour, numbers, and hands, respectively [ 23 ]. The total score ranged from zero to three points, and participants scoring zero to one were diagnosed with cognitive impairment.…”
Section: Methodsmentioning
confidence: 99%